Uczony i czarodziej. Zmienne koleje losu mistrza Starewicza - Sitkiewicz, Paweł (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Scientist and Wizard. The Vicissitudes of Maestro Starewicz The article is devoted to Władysław Starewicz (aka Ladislas Starewitch or Starevich), an animated film pioneer and independent filmmaker of Polish origin working for Russian, French and German cinematographies. The author attempts to explain why this multitalented artist and one of the most signifi cant puppet animators in film history did not achieve the commercial success he deserved, and shortly aft er WWII was almost totally forgotten. The article focuses on three aspects of Starewicz’s biography: his struggles with twentieth-century history, his fight for artistic and financial independence, and his eccentric personality. Finally, he is presented as a tragic figure who represents a model biography of an animator in Eastern Europe trying to achieve success in the Western world before 1945.